Web-Based Language Learning: Benefits for Enhancing EFL Learners’ Speaking Skill - Iwan Fauzi; Rudi Hartono; Widhiyanto Widhiyanto; Hendi Pratama (Universitas Negeri Semarang, 2022)
Computer-assisted language learning (CALL) achieves the outstanding position in the field of pedagogy of English as a Foreign Language (EFL). Its promising existence has encouraged foreign language learners to interact authentically in the computer-based English learning. Web-based language learning (WBLL) as the successor of CALL has emerged and is gaining its popularity as an online learning platform in the field of language education today. WBLL is able to improve the competence of learners and become a convincing interactive learning medium in confirming better quality of language input and output through the internet technology. Although not a few studies have discussed Web 2.0 technology, the majority of their findings may only review the students’ and teachers’ perceptions in using the technology; instead, not too many findings focus on how WBLL impacts learners’ language skills, more specifically EFL learners’ oral performance. This paper purports to review empirical studies using WBLL for enhancing EFL learners’ speaking skill in addition to its benefits for enhancing learners’ motivation and providing stimulus to alleviate their anxiety while speaking with highly interactive learning environment outside the classroom.